2021
DOI: 10.1016/j.dcn.2021.100914
|View full text |Cite
|
Sign up to set email alerts
|

Attachment security and striatal functional connectivity in typically developing children

Abstract: Attachment security is formed through interactions with a main caregiver during the first three years of life and reflects inter-individual differences in mental representations for the relationship. The striatum is known to be a key structure to initiate attachment behaviours and maintain attachment relationships as well as to modulate reward-related processing as part of the approach module in current neurobiological models of human attachment. Although findings have suggested critical roles of the striatum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 82 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…This is not surprising, given that the prefrontal cortex is responsible for functions involved in self-regulation 53 . Furthermore, increased functional connectivity in temporo-limbic regions was observed in 9-year-old children with secure attachment in comparison to children with insecure attachment of the same age 54 . As correlations between maternal stress and co-sleeping have been demonstrated 55 56 .…”
Section: Discussionmentioning
confidence: 86%
“…This is not surprising, given that the prefrontal cortex is responsible for functions involved in self-regulation 53 . Furthermore, increased functional connectivity in temporo-limbic regions was observed in 9-year-old children with secure attachment in comparison to children with insecure attachment of the same age 54 . As correlations between maternal stress and co-sleeping have been demonstrated 55 56 .…”
Section: Discussionmentioning
confidence: 86%
“…This is not surprising, given that the prefrontal cortex is responsible for functions involved in self-regulation 57 . Moreover, increased functional connectivity in temporo-limbic regions was observed in 9-year-old children with secure attachment in comparison to children with insecure attachment of the same age 58 .…”
Section: Discussionmentioning
confidence: 86%
“…example, functional connectivity has been utilised to investigate attachment styles in adolescents [63]. It was observed that adolescent attachment styles were negatively associated with caudate-prefrontal connectivity, but positively with the putamen-visual area connectivity [63]. Both named areas were also influenced by the onset of internet addiction, possibly providing a connection between the two.…”
Section: Plos Mental Healthmentioning
confidence: 99%